Design of interactive multimedia course in data structures & algorithms - Leong, Lester Kah Soon (2015)
As technology advances, our lives have been filled with multimedia and interactive devices. In order to fully engage users, a website must be simple and efficient for them to get hold of the information. The E-learning website will help students to engage in activities, interaction and make them understand the topic well. The report will cover the methodology used, research findings, and lastly conclusion.